Formation of political power institutions to ensure sustainable development of society - Nurmurod Abduyusupovich Djurayev (Genius Journals, 2024)
The article deals with the formation of institutions of political power and governance in order to ensure sustainable development of society. The definitions of the concepts of “political power” and “sustainable development” are given, the factors influencing their realization in the modern civil society are given, and the development strategy of the new Uzbekistan for 2022-2026 is analyzed
Keywords: Political Power; Political Control; Sustainable Development